Project SEARCH for Youth With Autism Spectrum Disorders: Increasing Competitive Employment On Transition From High School. (July 2013) - Wehman, Paul; Schall, Carol; McDonough, Jennifer; Molinelli, Alissa; Riehle, Erin; Ham, Whitney; Thiss, Weston R.
Supporting youth with autism spectrum disorder (ASD) in the transition to adulthood is challenging. This article provides a description of how Project SEARCH, a model transition program for youth with disabilities, was used to help youth with ASD gain competitive employment. This article includes two case studies and a thorough description of the additional supports provided to increase successful employment on graduation from high school. Key Project SEARCH program components include setting a goal for employment, providing successive intensive internships in a community business, and assuring collaboration between school and adult services staff. Supports specific to students with ASD include providing intensive instruction in social, communication, and job skills; visual supports; and work routine and structure. These supports are described in the provided case studies.